Pengaruh Affective Commitment dan Dukungan Atasan Terhadap Kinerja Karyawan - Sri Ekowati; Meilaty Finthariasari Finthariasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to determine the extent of the influence of affective commitment and supervisor support on employee performance either simultaneously or partially at PT. Bukit Angkasa Makmur, Bengkulu Tengah and to find out which factors are the most dominant influencing employee performance. The object of this research is the employees of PT. Bukit Angkasa Makmur, Central Bengkulu with a total of 110 respondents. Data were collected using a questionnaire and processed using SPSS 24. The results of this study obtained the equation Y = 3.677 + 0.661 X1 + 0.666 X2. The results of the analysis of the partial hypothesis test (t test) showed that the Affective Commitment variable was 4,520 with sig. 0.000 and Supervisor Support of 4.652 with sig.0.000 partially significant effect on employee performance of PT. Bukit Angkasa Makmur, Central Bengkulu. Simultaneous hypothesis testing using the f test shows that the Affective Commitment and Superior Support has an f value of 90.019 with a sig value. 0.000, it can be concluded that Affective Commintment and Support from superiors simultaneously affect the performance of employees of PT. Bukit Angkasa Makmur, Central Bengkulu.